DOUBLE-LAYER DIAMOND-LIKE CARBON ANTIREFLECTION COATINGS FOR GaAs SOLAR CELLS - Hovhannisyan, A. S.; Kh. S. Martirosyan; V. M. Aroutiounian; P. G. Soukiassian
There are many methods for improvement of performance of semiconductor solar cells (SC). One of them is the reduction of reflectance from SC surface. For this purpose different type thin-film coatings are used. Such an approach leads to enlargement of the absorbed part of solar irradiation in the whole optical and near IR regions when the corresponding antireflection coating (ARC) with appropriate refractive index (n) and layer thickness (d) is chosen.
Keywords: Physics; Interfaces; Electronic structure and electrical properties of surfaces; Low-dimensional structures